(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
A person’s or a community’s related emissions is an indication of the number of energy needed to produce their commodities. However, data shows that it only lasts for a short period of time. There has been much criticism of the assumptions behind the footprint assessments; here authors offer more evidence that obvious economic principles are not being fulfilled, because both the theory and historical realities contradict the fundamental assumptions. Indeed, writers contend that the trace arbitrarily refers to both zero non-ideal ghgs as well as zero carbon dioxide emissions, and national boundaries, making it difficult to extrapolate from the average ecological footprint. Therefore, intensive development may not be taken into account in the footprint and comparisons of bio-capacity stand flawed. One may make the case that, based on the principles of a footprint, the planet supports significantly increased production, but fundamental limitations such as land erosion do not resolve the footprint. Last but not least, Environmental footprints are obscured by a lack of linkage between land deterioration and the environmental impact. Better environmental measurements will address these issues in particular. Although, various research has been done earlier in this field but there are vital opportunities of more research and investigation in this domain in the future.